3‐Methylglutaconic aciduria—lessons from 50 genes and 977 patients. Issue 6 (25th January 2013) - Wortmann, Saskia B.; Kluijtmans, Leo A. J.; Rodenburg, Richard J.; Sass, Jörn Oliver; Nouws, Jessica; van Kaauwen, Edwin P.; Kleefstra, Tjitske; Tranebjaerg, Lisbeth; de Vries, Maaike C.; Isohanni, Pirjo; Walter, Katharina; Alkuraya, Fowzan S.; et al.
Abstract: Elevated urinary excretion of 3‐methylglutaconic acid is considered rare in patients suspected of a metabolic disorder. In 3‐methylglutaconyl‐CoA hydratase deficiency (mutations in AUH ), it derives from leucine degradation. In all other disorders with 3‐methylglutaconic aciduria the origin is unknown, yet mitochondrial dysfunction is thought to be the common denominator. We investigate the biochemical, clinical and genetic data of 388 patients referred to our centre under suspicion of a metabolic disorder showing 3‐methylglutaconic aciduria in routine metabolic screening. Furthermore, we investigate 591 patients with 50 different, genetically proven, mitochondrial disorders for the presence of 3‐methylglutaconic aciduria. Three percent of all urine samples of the patients referred showed 3‐methylglutaconic aciduria, often in correlation with disorders not reported earlier in association with 3‐methylglutaconic aciduria (e.g. organic acidurias, urea cycle disorders, haematological and neuromuscular disorders). In the patient cohort with genetically proven mitochondrial disorders 11 % presented 3‐methylglutaconic aciduria. It was more frequently seen in ATPase related disorders, with mitochondrial DNA depletion or deletion, but not in patients with single respiratory chain complex deficiencies. Besides, it was a consistent feature of patients with mutations in TAZ, SERAC1, OPA3, DNAJC19 and TMEM70 accounting for mitochondrial membrane related pathology. 3‐methylglutaconic aciduria is found quite frequently in patients suspected of a metabolic disorder, and mitochondrial dysfunction is indeed a common denominator. It is only a discriminative feature of patients with mutations in AUH, TAZ, SERAC1, OPA3, DNAJC19 TMEM70 . These conditions should therefore be referred to as inborn errors of metabolism with 3‐methylglutaconic aciduria as discriminative feature.